Reflections on the theoretical construction of the affectivity category - Varona Domínguez, Freddy (Pensamiento. Revista de Investigación e Información Filosófica, 2023)
The focus of this essay is the theoretical construction of the affective category, which is conceived as a system formed by emotions, feelings and passions, from which reflections are also developed around its theoretical elaboration. This study unfolds from a philosophical perspective and with a totalizing perspective. Some of the theoretical elaborations of essential authors are part of the content to understand these issues and discuss them, among which are Juan Luis Vives, Renato Descartes, David Hume (who is given a more careful attention) and Adam Smith; However, criteria of some contemporary scholars are also part of the content, such as the Italian philosopher Remo Bodei and the Spanish philosopher José Antonio Marina. When deepening in the referred categories, relations with human faculties are established, like the imagination, as well as with the values, the culture and the human improvement.